(untitled) (Journal of the College of Basic Education, 2024)
A myocardial infarction (MI), is the irreversible death (necrosis) of heart muscle commonly known as a heart attack. Acute myocardial infarction (AMI) occurs when blood flow decreases or stops to the coronary artery of the heart, causing damage to the heart muscle. MI is associated with an intelligible imbalance in oxidative stress. After myocardial injury, many cardiac biomarkers become detectable in venous circulation such as cardiac enzymes. The study’s main goals were to evaluate the clinical significant change in cardiac enzymes and investigate the positive and negative correlation with some serum oxidative stress markers total oxidative state (TOS), free amine and total antioxidant capacity (TAC) in patient and control groups. This study contained 120 subjects who were divided evenly into patients and control groups for the period between July and September 2022. The serum levels of oxidative stress markers were measured manually using spectrophotometer (model, Cecil, CE10N / England). The activity of cardiac enzymes and lipid profile were also determined by using Spectrophotometric kits supplied from Biolabo, France. The study showed that TOS had a significantly positive correlation with CK (r = 0.269*, p= 0.038) and ALT (r = 0.259*, p= 0.046), also for free amine, TnI (r = 0.287*, p= 0.026). Moreover, cardiac Troponin had highly positive correlation with oxidants and enzymes of the cardiomyocyte.